Influence of Peer Feedback on Motor Skill Learning and Self-Efficacy among Adolescents in Kenya - Oloo, Joan (International Journal of Physical Education, Recreation and Sports, 2024)
Purpose: The aim of the study was to influence of peer feedback on motor skill learning and self-efficacy among adolescents in Kenya Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on the influence of peer feedback on motor skill learning and self-efficacy among adolescents in Kenya found that peer feedback had a significant positive impact on motor skill learning. Adolescents who received feedback from their peers demonstrated improved motor skill performance compared to those who did not. Additionally, the study revealed that peer feedback also had a positive influence on self-efficacy, with adolescents reporting increased confidence in their motor skill abilities after receiving feedback from their peers Unique Contribution to Theory, Practice and Policy: Social cognitive theory, self-determination theory & feedback intervention theory may be used to anchor future studies on influence of peer feedback on motor skill learning and self-efficacy among adolescents in Kenya. Peer mentorship programs can create a structured framework for peer feedback and skill development, facilitating a sense of camaraderie and cooperation among adolescents. Educational policymakers should consider incorporating guidelines for peer feedback into curriculum standards for physical education.